2019
DOI: 10.3389/fonc.2019.00898
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of a Novel Eight-lncRNA Signature to Improve Prognostic Prediction in Head and Neck Squamous Cell Carcinoma

Abstract: Objectives: LncRNAs are essential survival prognostic indicators with important biological functions in tumorigenesis and tumor progression. This study aimed to establish a long non-coding RNA (lncRNA) signature that can effectively predict the prognosis of patients with head and neck squamous cell carcinoma (HNSCC) and explore the potential functions of these lncRNAs.Materials and Methods: We re-annotated RNA sequencing and obtained exhaustive RNA-seq data of 269 patients with comprehensive clinical informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The purpose of the risk score is to determine a uniform signature for subsequent prognostic prediction. The risk score formula was as follows ( Cheng et al, 2015 ; Yang et al, 2019 ): …”
Section: Methodsmentioning
confidence: 99%
“…The purpose of the risk score is to determine a uniform signature for subsequent prognostic prediction. The risk score formula was as follows ( Cheng et al, 2015 ; Yang et al, 2019 ): …”
Section: Methodsmentioning
confidence: 99%
“…At present, lncRNAs and miRNAs are believed to play an important role in tumorigenesis and have been identified as potential prognostic markers for HNSCC. Yang et al [ 8 ] established an 8-lncRNA signature associated with the prognosis of HNSCC, and Hess et al [ 9 ] identified prognostic 5-miRNA signature to independently predict disease control and survival in HNSCC patients. However, autophagy, as a crucial mechanism in tumorigenesis and progression, has not been studied on the effect of autophagy-associated genes on the prognosis of HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…They are involved in gene expression regulation at both the transcriptional and translational levels, and participate in tumorigenesis and tumor metastases [ 112 , 113 ]. Therefore, lncRNAs expression are promising biomarkers of cancer detection and expansion [ 114 ]. LncRNAs are found to play an important role also in HNSCC development.…”
Section: The Hnscc Epigenetic Landscape and Its Clinical Implicatimentioning
confidence: 99%